Sistem Otomatisasi Wiper Dan Lampu Pada Helm Berbasis Arduino UNO Disimulasiskan Dengan Simulator Hujan - Zainul Haque, Sahlan (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
Helmet is a security facility needed when driving, to maintain safety and protect the head from collisions in the event of a traffic accident. Helmets can also protect the head from the hot sun or rain and also protect the eyes from dust and pollution. A microcontroller is a chip that functions as a controller or control of electronic circuits and can generally store programs in it, programs on the microcontroller can be erased and rewritten. Arduino is open source, and has hardware and software that is easy to use. Arduino can recognize the surrounding environment through various types of sensors and can control lights, motors, and various other types of actuators. In some conditions the use of this helmet also has drawbacks, such as glass that is covered by water when it rains and a less clear view at night due to lack of lighting which causes limited visibility so that it can interfere with concentration while driving. Therefore, it is necessary to automate the process of making wipers and automatic lights on helmets so that they can clean rainwater automatically and provide remote lighting at night so as to increase concentration while driving.